2012
DOI: 10.4269/ajtmh.2012.11-0073
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Distribution of the Sand Flea Tunga penetrans in Wistar Rats and Humans in Two Endemic Areas in Brazil

Abstract: Abstract. Tungiasis is a zoonosis caused by Tunga penetrans. In Brazil, tungiasis is endemic in many resource-poor communities, in which various domestic and sylvatic animals act as reservoirs. Eighty laboratory-raised Wistar rats were exposed to T. penetrans in areas of intense transmission: a fishing village and an urban shantytown in Ceará State, northeast Brazil. The topographic distribution of lesions in Wistar rats was compared with the distribution of lesions in humans in the same area. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Unlike humans, where sand fleas localise randomly at various sites of the feet [ 10 , 28 , 29 ], this study has revealed that in the case of pigs and dogs, sand fleas on feet preferentially embed at claw coronary bands and nail basement, respectively. Similar to Wistar rats [ 26 ], both pigs and dogs, had more lesions on hind than front legs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike humans, where sand fleas localise randomly at various sites of the feet [ 10 , 28 , 29 ], this study has revealed that in the case of pigs and dogs, sand fleas on feet preferentially embed at claw coronary bands and nail basement, respectively. Similar to Wistar rats [ 26 ], both pigs and dogs, had more lesions on hind than front legs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed all lesions in infected dogs and the majority of lesions in pigs (99.3 %) were located on the limbs. Localization of sand fleas predominantly on feet is not unique to dogs and pigs but this is also the case in most susceptible animal species [ 26 ] and humans [ 10 , 27 ]. This has been attributed to the small size and poor jumping ability of sand fleas [ 9 ].…”
Section: Discussionmentioning
confidence: 99%